A study on the one-dimensional consolidation of double-layered structured soils. (March 2016) - Xie, Kang-He; Xia, Chang-Qing; An, Ran; Hu, An-Feng; Zhang, Wei-Peng
Abstract: The governing equations for the one-dimensional consolidation of double-layered structured soils under time-dependent loading are established in this paper. Using simplified k – σ ′ and m v – σ ′ models, the double-layered structured soils can be analyzed with three- or four-layered soils in which the thicknesses of the upper and lower layers change gradually. Approximate solutions for the governing equations are then obtained for two types of boundary conditions, and a computer program is developed. Using these solutions and the computer program, the consolidation behavior of double-layered structured soils is investigated.